Contribution of pheromones processed by the main olfactory system to mate recognition in female mammals - Baum, Micheal J. (Frontiers in Neuroanatomy, 2012)
Until recently it was widely believed that the ability of female mammals (with the likely exception of women) to identify and seek out a male breeding partner relied on the detection of non-volatile male pheromones by the female’s vomeronasal organ and their subsequent processing by a neural circuit that includes the accessory olfactory bulb, vomeronasal amygdala, and hypothalamus. Emperical data are reviewed in this paper that demonstrate the detection of volatile pheromones by the main olfactory epithelium of female mice which, in turn, leads to the activation of a population of glomeruli and abutting mitral cells in the main olfactory bulb (MOB). Anatomical results along with functional neuroanatomical data demonstrate that some of these MOB mitral cells project to the vomeronasal amygdala. These particular MOB mitral cells were selectively activated (i.e., expressed Fos protein) by exposure to male as opposed to female urinary volatiles. A similar selectivity to opposite sex urinary volatiles was also seen in mitral cells of the accessory olfactory bulb of female mice. Behavioral data from female mouse, ferret, and human are reviewed that implicate the main olfactory system, in some cases interacting with the accessory olfactory system, in mate recognition.